The effect of Store Image and Service Quality on Private Label Brand Image and Purchase Intention. Case Study: Lotte Mart Gandaria City - Rizkalla, Nosica; Suzanawaty, Leis (UI Scholars Hub, 2021)
Retailers produce their own private label brand as a strategy to distinguish their products from competitors’. Based on previous research, store image and service quality can be used to improve private label brand image and purchase intention. A Research is conducted at Lotte Mart, Gandaria City Mall in Jakarta to find out whether store image and service quality could influence private label brand image and purchase intention. This research adopts Wu et.al.'s framework (2010). Data processing uses Structure Equation Modeling. Research outcome reveals that service quality is a significant factor in influencing private label brand image and purchase intention.